Insights into the development of Ixodes scapularis: a resource for research on a medically important tick species - Katherine M. Kocan; José de la Fuente; Lisa A. Coburn (Parasites & Vectors, 2015)
Abstract Ticks (Acari: Ixodida) are arthropod ectoparasites dependent on a bloodmeal from a vertebrate host at each developmental stage for completion of their life cycle. This tick feeding cycle impacts animal health by causing damage to hides, secondary infections, immune reactions and diseases caused by transmission of pathogens. The genus Ixodes includes several medically important species that vector diseases, including granulocytic anaplasmosis and Lyme disease. I. scapularis, commonly called the black-legged or deer tick, is a medically-important tick species in North America and therefore was the first tick genome to be sequenced, thus serving as an important resource for tick research. This Primer focuses on the normal developmental cycle and laboratory rearing of I. scapularis. Definition of normal morphology, along with a consistent source of laboratory-reared I. scapularis, are fundamental for all aspects of future research, especially the effects of genetic manipulation and the evaluation of tick vaccine efficacy. Recent research important for the advancement of tick research, namely the development of tick cell culture systems for study of ticks and tick-borne pathogens, RNA interference for genetic manipulation of ticks and discovery of candidate antigens for development of tick vaccines, are briefly presented along with areas to target for future research.